2018
DOI: 10.1186/s12940-018-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in plasma levels of perfluoroalkyl substances (PFASs) are related to increase in carotid intima-media thickness over 10 years – a longitudinal study

Abstract: BackgroundIt has previously been reported that the environmental contaminants perfluoroalkyl substances (PFASs) are linked to atherosclerosis in cross-sectional studies. Since cross-sectional studies could be subject to reverse causation, the purpose of this study was to analyze if the longitudinal changes in PFASs during a 10-year follow-up were related to the change in carotid artery intima-media thickness (IMT, ultrasound) during the same period.MethodsIn the Prospective Investigation of the Vasculature in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…PFNA, PFDA, and PFUA, were all related to intima-media thickness in women, while the relationship was negative in men. The plasma concentration of PFUA was significantly related to carotid plaque in women (odds ratio 1.59), but not in men (odds ratio 0.93) (20).…”
Section: Pfas Cardiovascular Damage and Cardiovascular Events: Epidemiological Evidencementioning
confidence: 88%
See 1 more Smart Citation
“…PFNA, PFDA, and PFUA, were all related to intima-media thickness in women, while the relationship was negative in men. The plasma concentration of PFUA was significantly related to carotid plaque in women (odds ratio 1.59), but not in men (odds ratio 0.93) (20).…”
Section: Pfas Cardiovascular Damage and Cardiovascular Events: Epidemiological Evidencementioning
confidence: 88%
“…In the Prospective Investigation of the Vasculature in Uppsala Seniors (PIVUS) study, a total of 602 participants were investigated every 5-years starting at 70 years of age. The baseline concentrations of 6 different PFAS were significantly associated with the increase in carotid intima-media thickness over a 10-year follow-up, even after adjustment for traditional cardiovascular risk factors (20).…”
Section: Pfas Cardiovascular Damage and Cardiovascular Events: Epidemiological Evidencementioning
confidence: 93%
“…58 In a longitudinal analysis of the same cohort over 10 years, the change in all of the evaluated PFASs (perfluoroheptanoic acid, PFNA, perfluorodecanoic acid, PFUnDA, PFHxS, PFOS, PFOA, and perfluorooctane sulfonamide) were more or less related to the change in IMT. 59 In the latter study, no differences between men and women were seen. In both of these studies the relationships were significant also after adjustment for traditional risk factors, like blood pressure, LDL and HDL cholesterol, triglycerides, diabetes or smoking.…”
Section: Contaminants and Lipids: A Reviewmentioning
confidence: 70%
“…Human subjects with elevated intimate-media thickness have a high expression of P-selectin, underlying their role in atherosclerosis development [95]. The latest epidemiological findings have found that increases in plasma levels of six PFCs measured were substantially related to changes in carotid intima-medium thickness (increased to 0.058 mm) over the 10-year follow-up period [96]. The in vitro research elucidated the potential triggering effect of PFOA on platelets by examining the expression of P-Selectin in both resting platelets and TRAP-6 active platelets at concentrations ranging from 26 ng/mL to 400 ng/mL after exposure to PFOA [79].…”
Section: Discussionmentioning
confidence: 99%